ESENSI PROGRAM BIMBEL MANASIK HAJI UPAYA PEMBERDAYAAN MASYARAKAT - Abdul Choliq (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2018)
Hajj is the perfect worship of the pillars of Islam that became the goal of all Muslims in the world. So many hajj pilgrims who register to go to the Holy Land every year. Hajj implementation annually put aside various problems. One of them is not the optimal of the hajj manasik given by Ministry of Religion and the long departure time of hajj, while the candidate is dominated by the elderly (elderly). The ministry has a great desire to form an independent hajj, so becomes an important issue to be observed. Writing scientific paper aims to provide a good view to the Ministry of Religious Affairs or the guidance of pilgrimage to provide hajj manasik not just a manasik in general, but really oriented to empowering prospective pilgrims to form an independent hajj. Some of things that must be done is first to use the right methods such as Affirmation and Repetition and PAIKEM, both utilizing long waiting times with useful activities.Such as training in making signs of haj pilgrimage (such as marking ribbons, masks, or slendang neck), training planting of live pharmacies, and making some goods to prepare for the departure of pilgrimage (eg small bags for storage of goods and others). Third is to grow independent congregations in a way more opportunities to meet with other congregations in order to grow optimism in prospective pilgrims. ==================================================Haji merupakan ibadah penyempurna rukun Islam yang menjadi tujuan seluruh muslim di dunia. Sehingga setiap tahun banyak jama’ah haji yang mendaftarkan diri untuk berangkat ke Tanah Suci. Pelaksanaan Haji setiap tahunnya menyisihkan problematika bermacam-macam, salah satunya ialah belum optimalnya manasik haji yang diberikan oleh Kemenag dan waktu tunggu keberangkatan haji yang lama, sedangkan calon jamaah di dominasi oleh lansia (orang lanjut usia). Kementrian sendiri memiliki keinginan besar untuk membentuk haji mandiri, maka demikian itu menjadi permsalahan yang penting untuk di teliti. Penulisan karya tulis ilmiah ini bertujuan untuk memberikan pandangan baik kepada Kemenag atau bimbel haji agar memberikan mansik haji tidak hanya sekedar manasik pada umumnya, tetapi betul-betul berorientasi pada pemberdayaan calon jamaah agar membentuk haji mandiri. Beberapa hal yang harus dilakukan ialah pertama menggunakan metode yang tepat seperti Affirmation and repetition dan PAIKEM, kedua memanfaatkan waktu tunggu yang begitu lama dengan kegiatan-kegiatan bermanfaat seperti Bersama-sama dalam pembuatan tanda-tanda perbekalan haji, seperti pembuatan tanda pita, masker, atau slendang leher, melatih penanaman tanaman apotik hidup, dan pembuatan beberapa barang untuk memepersiapkan keberangkatan haji, misalnya tas-tas kecil untuk penyimpanan barang dan lainnya. Ketiga ialah dengan menumbuhkan jamaah mandiri dengan cara lebih banyak memberikan peluang temu dengan jamaah lain agar tumbuh optimisme dalam diri calon jamaah.